2020
DOI: 10.1124/dmd.119.090407
|View full text |Cite
|
Sign up to set email alerts
|

Stereoselective Bupropion Hydroxylation by Cytochrome P450 CYP2B6 and Cytochrome P450 Oxidoreductase Genetic Variants

Abstract: Bioactivation of the antidepressant and smoking cessation drug bupropion is catalyzed predominantly by cytochrome P4502B6 (CYP2B6). The metabolite hydroxybupropion derived from t-butylhydroxylation is considered to contribute to the antidepressant and smoking-cessation effects of the parent drug.Bupropion hydroxylation is the canonical in vitro and in vivo probe for CYP2B6 activity. P450 also requires obligate partnership with P450 oxidoreductase (POR). Human CYP2B6 and POR genes are highly polymorphic. Some C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
20
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(21 citation statements)
references
References 50 publications
1
20
0
Order By: Relevance
“…In this case, an altered production of 4-OH-OTA compared to other OTA metabolites might have consequences on OTA’s TK and TD, and this would require further investigation. Broadly speaking, TK consequences associated with these specific CYP2D6 alleles have been extensively reported from the literature for a wide range of probe substrates, and consequences on TD have also been demonstrated, particularly for pharmaceuticals [ 6 , 9 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this case, an altered production of 4-OH-OTA compared to other OTA metabolites might have consequences on OTA’s TK and TD, and this would require further investigation. Broadly speaking, TK consequences associated with these specific CYP2D6 alleles have been extensively reported from the literature for a wide range of probe substrates, and consequences on TD have also been demonstrated, particularly for pharmaceuticals [ 6 , 9 , 27 , 28 , 29 ].…”
Section: Introductionmentioning
confidence: 99%
“…The CYP2B6*4 allele contributed to increased activity in efavirenz 8-hydroxylation and to reduced plasma concentration of efavirenz in HIV-infected patients 15 , 18 ; however, dose modification was not required for efficient efavirenz therapy 23 . Intrinsic clearance of both bupropion enantiomers was minimally increased by CYP2B6*4 , whereas pharmacokinetic studies demonstrated significantly high bupropion clearance in vivo and consequently high hydroxy-bupropion exposure in CYP2B6*4 carrier subjects 17 , 61 , 66 . Interestingly, CYP2B6*4 displayed lower cyclophosphamide 4-hydroxylation activity in vitro than CYP2B6*1 18 , 63 ; however, CYP2B6*1/*4 genotype appeared to have no impact on 4-hydroxy-cyclophosphamide formation in vivo comparing to CYP2B6*1/*1 64 .…”
Section: Discussionmentioning
confidence: 95%
“…41 In wild-type CYP2B6.1, the lysine262 side chain is not able to form similar hydrogen bonds with the neighbouring residues. This may account for the differences in methadone 27 artemether, 45 and selegiline, 46 but not bupropion, 44 ketamine, 26 nicotine, 43 cyclophosphamide 47,48 and ifosfamide. 49,50 CYP2B6 variant activity for methadone appears most similar to that for efavirenz among the various CYP2B6 substrates evaluated.…”
Section: Discussionmentioning
confidence: 99%